A rule-based theoretical account of social stories to address the double empathy problem - Camilleri, Louis John; Maras, Katie; Brosnan, Mark (Frontiers in Psychology, 2023)
Social StoriesTM (SS) is one of the most popular and researched interventions for autistic children. To date, research that focuses on outcomes has been prioritised over the investigation of the psychological mechanisms that inform the intervention. In this article, we consider theoretical accounts proposed thus far which could underpin SS. We argue that mechanisms that are based on social deficit theories lack validity, and propose a rule-based theoretical account to inform a strengths-based approach towards conceptualizing the mechanisms that underpin SS. We apply this account to the ‘double-empathy problem’ to propose that SS can be adapted to involve all parties in the development and delivery of SS support by adopting a rule-based perspective. We use the example of systemizing (the drive to analyse and explore systems in terms of ‘if-and-then’ rules), which is proposed to be a relative autistic strength, as a form of rule-based thinking that can provide a theoretical account of SS and a framework to address the double-empathy problem.